Persepsi mahasiswa terhadap penggunaan ChatGPT dalam mengembangkan keterampilan berfikir kritis - Sariyati Sariyati (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study investigates university students’ perceptions of the use of ChatGPT in developing critical thinking skills through a descriptive phenomenological approach. Data were gathered via in-depth interviews with eight students from various disciplines at Institut Az Zuhra Pekanbaru and analyzed using Colaizzi’s method. The results show that ChatGPT serves as a supportive tool for understanding concepts, constructing arguments, and engaging in critical comparison of ideas. Participants also reported increased motivation, curiosity, and reflective thinking. However, some concerns were noted, including dependency on the tool, diminished active thinking, and risks of academic dishonesty. The study highlights the dual role of AI in education—both as a catalyst for learning and as a potential source of ethical challenges. It emphasizes the importance of responsible and guided use of AI tools like ChatGPT in higher education to maximize their benefits while minimizing negative impacts.